사이버대학생들의 학업스트레스와 성취도의 관계에서 학업적 자기효능감, 과제가치의 조절효과 - 주영주(Joo Young Ju); 이정원(Lee Jeongwon); 조선유(Cho Sunyu) (평생학습사회, 2012)
본 연구에서는 사이버대학생들의 학업스트레스와 성취도의 관계에서 학업적 자기효능감과 과제가치의 조절효과를 규명하고자 하였다. 사이버대학생들은 상호작용 기회의 부족, 학업에만 열중할 수 없는 상황, 학교의 지원 부족, 주변사람으로부터의 낮은 인지도, 많은 강의 내용과 과제물 등으로 학업 상의 어려움을 겪고 있으며, 이는 학업스트레스를 유발하여 성취도에 부정적인 영향을 미친다. 따라서 본 연구에서는 사이버대학생들의 학업스트레스와 성취도의 관계에서 학업스트레스의 부정적인 영향을 조절할 수 있는 변인들에 대한 탐색이 이루어졌다. 이를 위해 W사이버대학의 2011학년 2학기 사찰음식 과목에 등록한 253명을 대상으로 설문을 실시하였으며, 수집된 데이터를 바탕으로 위계적 중다회귀분석을 실시하였다. 연구결과, 첫째, 학업스트레스는 성취도를 유의미하게 예측하는 것으로 나타났다. 둘째, 학업적 자기효능감은 성취도를 유의미하게 예측하였으나, 학업스트레스와 성취도 간에 조절효과를 가지지 못하는 것으로 나타났다. 셋째, 과제가치는 학업스트레스와 성취도 간에 조절효과를 나타내었다. 즉, 과제가치가 높은 집단에 비해 과제가치가 낮은 집단의 학업스트레스와 성취도 간의 설명력이 더 강했다. 연구결과를 바탕으로 도출된 시사점으로는 첫째, 사이버대학생들의 학업스트레스를 줄이기 위해 상담인력의 배치가 필요하다는 점이다. 둘째, 사이버대학생들의 학업적 자기효능감과 과제가치를 높일 수 있는 구체적인 방안이 마련되어야 한다는 점이다. The present study investigated the moderating effects of academic self-efficacy and task-value on the main effect of academic stress to the achievement in cyber university. Cyber university students are experiencing hardships such as lack of interaction, individual' difficult situation, lack of administrative support, low recognition and lots of lecture contents. These hardships cause academic stress, and affect negatively on achievement. So this study investigated moderating variables between academic stress and achievement. For this study, W cyber university in Korea was chosen. The subjects were 253 students who enrolled in the fall semester of 2011. The results of Step-wise multiple regression analysis are as follows. First, academic stress predicted significantly on achievement. Second, although academic self-efficacy predicted significantly on achievement, academic self-efficacy did not perform as moderator between the major variables. Third, the moderating effect of task-value was evidenced. Based on the result of this study, following suggestions were proposed. First, it needs to place counselors and advisors for decreasing academic achievement. Second, it is essential to create practical instructional strategies to increase self-efficacy and task value. KCI Citation Count: 30